ANALISIS PROGRAM KELUARGA HARAPAN DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DESA ENTOGONG KECAMATAN KAYAN HULU - Rifka Pridiyanti; Mashudi Mashudi; Nuraini Asriati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis research aims to analyze the Program Keluarga Harapan (PKH) in the welfare of the community in the Entogong village. The method used is a qualitative method with a descriptive form. The data sources in this study were 3 village staff and 10 beneficiaries of village as an informant to conduct interviews. The results showed that 1) the PKH planning in the village was categorized as well according to the government's pre-determined enlisting. 2) The implementation of PKH with 5 aspects of a) well-categorized education(10 informants able to finance education), b) well-categorized health (8 people able to fulfill the need for health) c) the housing and environment are not well categorized (10 informants have not been able to improve the welfare of families), d) aspects and consumption patterns are not well categorized(10 informants have not been able to enhance the welfare of the family), e) poverty is categorized not good (6 have not been able to reduce poverty). 3) evaluation from the implementation of PKH in the village has been functional through education and health but has not been able to improve the prosperity through housing and environment, the level and pattern of consumption and poverty Keywords: Community Welfare, Program Keluarga Harapan (PKH)